2019
DOI: 10.3390/ijms20123044
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Expression Analysis, and Subcellular Localization of Carthamus tinctorius bHLH Transcription Factors

Abstract: The basic helix–loop–helix (bHLH) family is the second largest superfamily of transcription factors that belongs to all three eukaryotic kingdoms. The key function of this superfamily is the regulation of growth and developmental mechanisms in plants. However, the bHLH gene family in Carthamus tinctorius has not yet been studied. Here, we identified 41 bHLH genes in Carthamus tinctorius that were classified into 23 subgroups. Further, we conducted a phylogenetic analysis and identified 10 conserved protein mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 41 publications
6
18
0
Order By: Relevance
“…The most common cis-element observed in DobHLH gene promoters was the G-box, which can respond to light. Similar results were found in other species such as C. tinctorius [ 48 ] and maize [ 28 ]. The second most common types of cis-elements in DobHLH genes were the hormone-responsive motifs that responded to MeJA, ABA, and ethylene.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The most common cis-element observed in DobHLH gene promoters was the G-box, which can respond to light. Similar results were found in other species such as C. tinctorius [ 48 ] and maize [ 28 ]. The second most common types of cis-elements in DobHLH genes were the hormone-responsive motifs that responded to MeJA, ABA, and ethylene.…”
Section: Discussionsupporting
confidence: 89%
“…We found that four clades in Arabidopsis were not present in D. officinale . The similar results were found in other plants such as C. tinctorius [ 48 ], apple [ 51 ], and wheat [ 42 ], which suggests those genes were lost during their evolution. Clades 14 and 15 of the bHLH family in D. officinale contained 14 and 15 members, respectively, which accounted for as many as 28.57% members of the family.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Based on the highly conserved bHLH domain, the bHLH superfamily is categorized into two main groups: the basic region and the HLH region. The basic region is a DNA-binding interface located next to the N-terminus of the protein domain, whereas the HLH region serves as the dimerization domain and consists of two amphipathic α-helices linked by a loop [32]. Apart from the high frequency of bHLH conserved domains, some other motifs also occur within the bHLH superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the highly conserved domains and their evolutionary relationships, this superfamily is mainly divided into 20-25 subfamilies in agronomically important plants. A wide range of extensive studies have been reported on the bHLH superfamily-related genes in plant species after genome sequences have been produced, including cucumber [5], Arabidopsis [7], apple [10], tomato [24] and Carthamus tinctorius [32]. Additionally, functional and structural characterizations of most plant bHLH proteins have been described in detail.…”
Section: Discussionmentioning
confidence: 99%